Characterizing restless legs syndrome and leg motor restlessness in patients with Parkinson's disease: A multicenter case-controlled study. (November 2017) - Suzuki, Keisuke; Okuma, Yasuyuki; Uchiyama, Tomoyuki; Miyamoto, Masayuki; Sakakibara, Ryuji; Shimo, Yasushi; Hattori, Nobutaka; Kuwabara, Satoshi; Yamamoto, Toshimasa; Kaji, Yoshiaki; Hirano, Shigeki; Numao, Ayaka; et al.
Abstract: Background: We investigated the prevalence and impact of restless legs syndrome (RLS) and leg motor restlessness (LMR) in patients with Parkinson's disease (PD) in a multicenter study. Methods: A total of 436 PD patients and 401 age- and sex-matched controls were included in this study. RLS was diagnosed based on four essential features. LMR was diagnosed when a participant exhibited the urge to move his or her legs but did not meet the four essential features of RLS. Results: The RLS prevalence did not differ between PD patients and controls (3.4% vs. 2.7%), while LMR prevalence was significantly higher in PD patients than in controls (12.8% vs. 4.5%). PD patients with RLS or LMR had a higher prevalence of excessive daytime sleepiness (EDS) (50.7%, vs. 6.9%), probable REM sleep behavior disorder (38.0% vs. 3.4%) and PD-related sleep problems (49.3% vs. 20.7%) than controls with RLS or LMR. RLS/LMR preceding PD onset was related to an older age of PD onset. Conclusion: Our study revealed an increased prevalence of LMR but not RLS in PD patients. LMR could be an early manifestation of PD; however, whether LMR is within the range of RLS or whether LMR and RLS constitute different entities in PD requires further studies. Highlights: We studied the clinical correlates of RLS and leg motor restlessness (LMR) in PD. The prevalence of LMR, but not RLS, was higher in PD patients than in controls. PD with RLS or LMR was related to excessive daytime sleepiness and sleep problems. RLS/LMR preceding PD onset was related to an older age of PD onset. LMR could be an early manifestation of PD.